Quality Monitoring of PE-X Semi-Finished Products - Heiduk, Ines; Falk, Martin; Schubert, Dirk W.; Kaschta, Joachim (Kunststoffe International, 2015)
In industrial production monitoring, fast, reliable results are required to evaluate product quality. Suitable test methods must be available for this purpose. The time-consuming method previously used to determine the degree of crosslinking of PE-X pipes can now be replaced by rapid rheological measurements